Lower expression of plasma-derived exosome miR-21 levels in HIV-1 elite controllers with decreasing CD4 T cell count - María J. Ruiz-de-León; María A. Jiménez-Sousa; Santiago Moreno; Marcial García; Mónica Gutiérrez-Rivas; Agathe León; Marta Montero-Alonso; Juan González-García; Salvador Resino; Norma Rallón; José M. Benito; Alejandro Vallejo; et al. (Journal of Microbiology, Immunology and Infection, 2019)
Exosome-derived miR-21 was independently associated with CD4 T cell decline in HIV-1-infected elite controllers (OR 0.369, 95% CI 0.137–0.994, p = 0.049). Also, a negative correlation between miR-21 expression and MCP-1 level was found (r = −0.649, p = 0.020), while no correlation between soluble biomarkers or cellular immune activation was found. Keywords: Exosomes, miRNAs, HIV-1, Elite controllers, Immune activation, Soluble biomarkers